Echeveria munizii (Crassulaceae) a new species of epiphyte from tropical Volcán de Colima, Mexico - Vázquez-García, José Antonio; Nieves-Hernández, Gregorio; Padilla-Lepe, Jesús; Nuño-Rubio, Ana Teresa; Cházaro-Basáñez, Miguel De Jesús (Phytotaxa, 2014)
Echeveria munizii, a new species from the southwestern slopes of Volcán de Colima on the Colima-Jalisco border in western Mexico is described and illustrated. This species belongs to series Gibbiflorae and is most similar to E. fulgens from which it differs in having adaxially sulcate leaves with straight and hyaline margins, olive green to brownish green surface, a fewer flowered inflorescence with fewer flowers per branch, a pink / orange bicolored corolla with the inner surface pale pink to orange, the base of the carpels white, and longer pedicels. A species conservation assessment, undertaken using IUCN criteria, determines Echeveria munizii to be Critically Endangered (CR).